Student views of “ethical” issues: A situational analysis - Jones, William A. (Journal of business ethics, 1990)
This paper reports on selected attitudes of a sample of third-year undergraduate business students in a major urban university. The focus of the research is on respondent perceptions of certain aspects of the employee-employer relationship. Such issues as use of the company car for a personal trip, use of the company copy machine for personal copies, calling in sick when some personal time is needed, eating at the very best restaurant on a business trip and others are explored. Half of the students surveyed were asked to respond as though they were employees of the company. The other half were asked to respond as though they were the President of the company. Both groups seemed to reflect a certain amount of “flexibility” in their responses to the issues presented. The assumed position of the respondent, the “situation,” did influence the responses given.